Salt facts: public awareness, attitudes and practices in Sri Lanka. (30th September 2020) - Jayatilleke, A U; Gunawardena, N; de Silva, A; Wickramasinghe, C; Gamlath, L; Siriwardena, T; Wickramasinghe, A; Thalagala, I; Vidanapathirana, J; Pendse, R
Abstract: Recent national surveys have estimated that Sri Lankans are consuming much higher salt than the recommended 5 g/day. However, population-level knowledge, attitudes, and practices regarding dietary salts have not been assessed. This study was conducted with the objective of assessing the knowledge, attitude and practices related to salt consumption among adolescents aged 15-18 years and adults in Sri Lanka. We conducted a countrywide cross-sectional descriptive household survey among a nationally representative sample of 1016 adult and 505 adolescents aged 15-18 years selected from 10 of 25 districts, using a multi-stage cluster sampling method. We used an electronic, interviewer-administered multicomponent questionnaire for data collection. Of all respondents (n = 1521), only 40% were aware of the recommended limit of 5g/day or less. Importantly, 90% of adults and 86% of adolescents knew the adverse health effects of high salt intake. Discretionary salt was a major contributor to intake, with half the survey population (50%) adding salt when cooking rice, the staple food. Although the household monthly purchase of salt indicated the per-person consumption is double the recommended amount, 48% of adults and 46% of adolescents believed that they consume the correct amount of salt. A majority (72% of adults; 69% of adolescents) were of the view that it would be easy to reduce their salt intake. Most preferred (adults - 72%, adolescents - 69%) media source for health-related information was television. The majority of Sri Lankan adults and adolescents are not aware of the recommended limits for salt intake. The average salt consumption is double the recommended amount. Although the belief that 'the respondents consume the correct amount of salt' was common, it was encouraging to note that a majority had positive attitudes towards reducing their salt consumption'. Raising public awareness to reduce daily salt intake should use preferred media sources. Key messages: Sri Lankan adolescents and adults are not well aware of the recommended limits for salt consumption and consumed high amounts of dietary salt, mainly discretionary salt. Majority of the participant had positive attitudes, believing that they can easily reduce salt consumption, indicating opportunities for behavioral changes.